Immediate Weight Bearing of Plated Both-Bone Forearm Fractures Using Eight Cortices Proximal and Distal to the Fracture in the Polytrauma Patient Is Safe. Issue 15 (1st August 2021) - Marchand, Lucas S.; Horton, Steven; Mullike, Alexandra; Goel, Ritu; Krum, Nicole; Ochenjele, George; O'Hara, Nathan; O'Toole, Robert V.; Eglseder, W. Andrew; Pensy, Raymond
Abstract : Introduction: Rehabilitation of trauma patients is facilitated by surgical stabilization permitting weight bearing (WB) of the fractured extremity. Both-bone forearm fracture (BBFx) plate osteosynthesis is an accepted technique with high union and low complication rates; yet, postoperative WB protocols have not been adequately investigated. There exists concern for increased complications in plated BBFx fractures for patients prescribed immediate WB. We hypothesized that immediate WB of surgically treated BBFxs results in acceptable rates of complications. Methods: Patients presenting to a Level-1 trauma center from 2007 to 2016 with a BBFx were identified retrospectively. Patients were skeletally mature, surgically treated with prescribed immediate WB protocol, and followed for 6 months or to fracture union. Collected data included demographics, fracture characteristics, associated injuries, and WB protocols for all extremities. Complications recorded included nonunion, hardware failure, and infection. Standard statistical comparisons were used to evaluate the risk of complication in polytrauma patients with modified lower extremity WB protocols (polytrauma group) and patients with no lower extremity WB restrictions (isolated group). Results: Two hundred thirteen patients were included with 75 (35%) females and 138 (65%) males. Mean age was 40 years and mean follow-up was 46 weeks. There were 142 (67%) patients in the poly-trauma and 71 (33%) patients in the isolated groups. In the poly-trauma group 21 (10%) patients had bilateral lower extremity WB restrictions. There were 11 (6%) complications noted: 2 non-unions, 4 hardware failures, and 5 infections. Demographics did not vary between the two groups. There was no difference in complications in the isolated (5.7%) versus poly-trauma groups (5.0%) ( P = 0.75). Conclusion: Immediate WB rehabilitation after BBFx plate osteosynthesis seems to be safe and associated with low nonunion and complication rates. Our results demonstrate that polytrauma patients using ambulatory aids for lower extremity injuries can immediately WB without increased risk compared with isolated BBFx patients.